Malaika's costume - Hohn, Nadia L. (Groundwood Books : House of Anansi Press, 2016)
Participating in a first Carnival since her mother left to find a better job, Malaika fears she will not be able to dance in the parade without a costume and comes up with an idea to use scrap fabric to create a patchwork rainbow peacock outfit.